2014
DOI: 10.1007/s11064-014-1339-6
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Dependent Antioxidant Effects of Physical Exercise in the Hippocampus of Mice

Abstract: Exercise increases both the consumption of oxygen and the production of reactive species in biological tissues, and this is counterbalanced by antioxidant adaptations to regular physical training. When the intensity of exercise fluctuates between mild and moderate, it improves the status of reduction-oxidation balance in the brain and induces neuroplasticity. However, intense exercise can oxidize the brain and impair neurological function. The effect of the frequency of exercise, which is an important factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…This is consistent with physical exercise ameliorating the reduction‐oxidation (redox) balance in the CNS through improvements in the defensive mechanisms of antioxidants . Additionally, Speck et al showed that an adequate frequency of moderate‐intensity exercise (treadmill) caused antioxidant changes in the hippocampi of mice. Importantly, voluntary exercise attenuated METH‐induced oxidative stress in brain microvessels by raising antioxidant capacity of these capillaries, and protected against BBB disruption, in mice .…”
Section: Neurobiology Of Exercise On Meth Addiction Managementmentioning
confidence: 54%
“…This is consistent with physical exercise ameliorating the reduction‐oxidation (redox) balance in the CNS through improvements in the defensive mechanisms of antioxidants . Additionally, Speck et al showed that an adequate frequency of moderate‐intensity exercise (treadmill) caused antioxidant changes in the hippocampi of mice. Importantly, voluntary exercise attenuated METH‐induced oxidative stress in brain microvessels by raising antioxidant capacity of these capillaries, and protected against BBB disruption, in mice .…”
Section: Neurobiology Of Exercise On Meth Addiction Managementmentioning
confidence: 54%
“…Maternal swimming in contrast, appears to be a bad exercise for the pup's brain development. A positive outcome on brain maturity as well as metabolism depends on frequency, duration, and intensity of the exercise (Ploughman et al, 2007; Speck et al, 2014). Swimming is rather forced work out for rodents and studied as aerobic exercise to challenge the metabolism and immune system (Wasinski et al, 2013; Cunha et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It would be important to have information on the neurobiological changes caused by exercise that may have a positive effect on drug-addicted individuals. According to previous studies, the neurobiological changes that take place in METH users through physical exercise may be due to the interaction of various changes, including the regulation of CNS neurochemicals [ 17 , 30 ], improvement of defense mechanisms involving antioxidants [ 31 , 32 , 33 , 34 ], neurogenesis [ 35 ], glial formation [ 36 ], and protection of the blood–brain barrier [ 37 , 38 ]. However, the results presented in these previous studies do not fully explain the effect of exercise on METH-induced neurobiological changes.…”
Section: Introductionmentioning
confidence: 99%